2017
DOI: 10.1371/journal.pone.0171265
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent rearrangements of the Myb/SANT-like DNA-binding domain containing 3 gene (MSANTD3) in salivary gland acinic cell carcinoma

Abstract: Pathogenic gene fusions have been identified in several histologic types of salivary gland neoplasia, but not previously in acinic cell carcinoma (AcCC). To discover novel gene fusions, we performed whole-transcriptome sequencing surveys of three AcCC archival cases. In one specimen we identified a novel HTN3-MSANTD3 gene fusion, and in another a novel PRB3-ZNF217 gene fusion. The structure of both fusions was consistent with the promoter of the 5’ partner (HTN3 or PRB3), both highly expressed salivary gland g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
1
30
1
Order By: Relevance
“…The role of myb/SANT‐like DNA‐binding domain‐containing protein 3‐like, which was strongly expanded from 6 to 39 in the B. germanica genome, is not conclusively resolved. However, it also appears to regulate gene expression and protein synthesis in mammals (Barasch et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The role of myb/SANT‐like DNA‐binding domain‐containing protein 3‐like, which was strongly expanded from 6 to 39 in the B. germanica genome, is not conclusively resolved. However, it also appears to regulate gene expression and protein synthesis in mammals (Barasch et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Animal models and immunohistochemical studies have suggested that an upregulated mTOR pathway may be involved in the development of AcCCs . A 2017 study demonstrated recurrent rearrangements involving the Myb/SANT‐like DNA binding domain containing 3 ( MSANTD3 ) gene on chromosome 9q in 3 of 20 cases of AcCC …”
Section: Malignant Neoplasmsmentioning
confidence: 99%
“…76,77 A 2017 study demonstrated recurrent rearrangements involving the Myb/SANT-like DNA binding domain containing 3 (MSANTD3) gene on chromosome 9q in 3 of 20 cases of AcCC. 78 On FNAC, smears are highly cellular and consist of clusters of cells with slightly enlarged, eccentrically located nuclei, evenly distributed chromatin, and occasionally conspicuous nucleoli with abundant cytoplasm demonstrating coarse zymogen granules (Figure 7). Occasional stripped nuclei are common.…”
Section: Acinic-cell Carcinomamentioning
confidence: 99%
“…In PAC of classic type, the E710D hotspot mutation in exon 15 of the PRKD1 gene is unique to this tumor type, rearrangement of the PRKD1 ‐ 3 genes are described exclusively in PAC of cribriform type, and the HTN3 ‐ MSANTD3 fusion in acinic cell carcinoma has not been described in any other tumor type (Fig. D; ).…”
Section: Tumors Of the Salivary Glandmentioning
confidence: 95%
“…In PAC of classic type, the E710D hotspot mutation in exon 15 of the PRKD1 gene is unique to this tumor type, rearrangement of the PRKD1-3 genes are described exclusively in PAC of cribriform type, and the HTN3-MSANTD3 fusion in acinic cell carcinoma has not been described in any other tumor type ( Fig. 2D; [35][36][37]. The most promising venues for targeted therapy is in SC which consistently harbor fusions involving ETV6, with the most frequent fusion partner being NTRK3, and RET in a subset of cases ( Fig.…”
Section: Molecular Characteristics and Implications For Targeted Therapymentioning
confidence: 97%